Following the Path of Least Resistance - Donald G. Mitchell (Perspectives of Earth and Space Scientists)
Abstract The reason a path may be the path of least resistance is because it may be the path for which you are most suited. For you it may look like a stroll in the park; for someone else, it may look like climbing Everest. Or vice versa. Taking the “easy” route is not copping out; it is a form of playing to your strength. Here I detail my professional path from digging holes for antennas in graduate school to designer and builder of energetic neutral atom imagers that have flown and continue to fly throughout the heliosphere.